2012
DOI: 10.1161/circulationaha.111.086074
|View full text |Cite
|
Sign up to set email alerts
|

Adult Bone Marrow Cell Therapy Improves Survival and Induces Long-Term Improvement in Cardiac Parameters

Abstract: Background Despite rapid clinical translation and widespread enthusiasm, the therapeutic benefits of adult bone marrow cell (BMC) transplantation in patients with ischemic heart disease (IHD) continue to remain controversial. A synthesis of the available data is critical to appreciate and underscore the true impact of this promising approach. Methods and Results A total of 50 studies (enrolling 2,625 patients) identified by database searches through January 2012 were included. Weighted Mean Differences for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
349
6
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 427 publications
(373 citation statements)
references
References 75 publications
11
349
6
3
Order By: Relevance
“…Combining bioactive materials with stem cell products represents a natural extension of these approaches given recent meta-analyses demonstrating only modest persistence of injected stem cell products alone (approx. 1-2%) beyond 12 months [5,12,25,26]. As such, a variety of biomaterials have entered active development with the intent of providing a supportive scaffold that improves both acute cell retention and long-term cell viability [8,13,27].…”
Section: Discussionmentioning
confidence: 99%
“…Combining bioactive materials with stem cell products represents a natural extension of these approaches given recent meta-analyses demonstrating only modest persistence of injected stem cell products alone (approx. 1-2%) beyond 12 months [5,12,25,26]. As such, a variety of biomaterials have entered active development with the intent of providing a supportive scaffold that improves both acute cell retention and long-term cell viability [8,13,27].…”
Section: Discussionmentioning
confidence: 99%
“…[71] This finding is underlined by a recently published meta-analysis. [72] In this respect, large scaled phase 3 trials are on the way to identify the effects of BMMNCs on clinical outcome and mortality in patients with acute myocardial infarction or ischemic cardiomyopathy (BAMI, NCT01569178; REPEAT, NCT01693042). …”
Section: Bone-marrow-derived and Mobilized Cd34+ Cells For Cell-basedmentioning
confidence: 99%
“…[3][4][5][6] Only a small number of participants have been enrolled into most studies, but some meta-analyses have, nevertheless, been performed to evaluate the benefit of BMSC therapy for cardiac repair. [7][8][9] For example, in one meta-analysis the investigators included 50 studies (a total of 2,625 patients), and reported that BMSCs improved left ventricular ejection fraction (LVEF), reduced infarct size, and limited remodelling in patients with ischaemic heart disease (IHD), and that these benefits seemed to persist during long-term follow-up. 8 Similarly, the authors of a 2014 Cochrane Systematic Review, which included 23 randomized controlled trials involving 1,255 participants, reported that BMSC treatment can improve LVEF, mortality, and performance status in the long term (after at least 1 year) in individuals with IHD and heart failure.…”
mentioning
confidence: 99%
“…[7][8][9] For example, in one meta-analysis the investigators included 50 studies (a total of 2,625 patients), and reported that BMSCs improved left ventricular ejection fraction (LVEF), reduced infarct size, and limited remodelling in patients with ischaemic heart disease (IHD), and that these benefits seemed to persist during long-term follow-up. 8 Similarly, the authors of a 2014 Cochrane Systematic Review, which included 23 randomized controlled trials involving 1,255 participants, reported that BMSC treatment can improve LVEF, mortality, and performance status in the long term (after at least 1 year) in individuals with IHD and heart failure. 9 Meta-analyses are considered the highest level of evidence and might have a major effect on future health policy decisions; therefore, ensuring their accuracy is of paramount importance.…”
mentioning
confidence: 99%
See 1 more Smart Citation